Chemokines, molecular drivers of thromboinflammation and immunothrombosis - Leberzammer, Julian; von Hundelshausen, Philipp (Frontiers in Immunology, 2023)
Blood clotting is a finely regulated process that is essential for hemostasis. However, when dysregulated or spontaneous, it promotes thrombotic disorders. The fact that these are triggered, accompanied and propagated by inflammation is explained by the notion of thromboinflammation, in which inflammatory mediators, including chemokines, are of significant importance. Since vascular cells rather initiate and cellular surfaces are catalysers of these processes, this review will illuminate the role of chemokines in thrombosis from a cellular perspective, where endothelial cells, platelets, red blood cells, and leukocytes can be either the source or target of chemokines. Described are the biological mechanisms of action involving receptor-independent processes, binding to atypical chemokine receptors and binding and activating their cognate receptors, either driving cell activation or the classical G-protein-induced cell recruitment. Independent of binding to chemokine receptors to elicit signalling, chemokines can affect thrombosis by forming complexes with heparin, DNA, and other polyanions resulting in prothrombotic immune complexes that are pathognomonic for HIT and VITT or contribute to NET formation. They also alter the electrical charge of the cell surface of platelets and interact with coagulation factors, thereby modulating the balance of fibrinolysis and coagulation. Also independent of classical chemokine activity, chemokines activate cognate receptors on platelets and cause aggregation and thrombosis through the PI3Kβ and Btk pathways. Typical chemokine-chemokine receptor interactions are thought to underlie processes that contribute to endothelial adhesiveness to organize the massive accumulation of leukocytes on endothelium in the initial phase of thrombosis, reminiscent of atherogenesis in time-lapse. Later, the reorganization and resolution of a thrombus require coordinated cell migration and invasion of the thrombus, and, as such, indeed, chemokines recruit leukocytes to existing thrombi. However, our understanding of these thrombolytic processes is less developed.